Neuroendocrine prostate cancer or prostatitis? An unusual false positive on gallium-68 DOTA-Tyr3-octreotate positron emission tomography/computed tomography in a patient with known metastatic neuroendocrine tumor - Schmidt, Matthew Q; Trenbeath, Zachary; Chin, Bennett B (World Journal of Nuclear Medicine, 2019)
The importance of gallium-68 DOTA-Tyr3-octreotate (68Ga DOTATATE) positron emission tomography/computed tomography (PET/CT) in the imaging of neuroendocrine tumors (NETs) has grown substantially over the past decade and is becoming markedly more common. We present the case of a male with known metastatic NET who underwent 68Ga DOTATATE PET/CT for restaging, incidentally revealing intense uptake of the prostate with a maximum standard uptake value of 17.4. Due to the patient's medical history, this finding was concerning for neuroendocrine prostate cancer. However, core biopsies of the prostate were negative for malignancy and positive for chronic inflammation. Chronic prostatitis is a very common condition in adult males and is often asymptomatic. Inflammatory conditions, including prostatitis, are important causes of false-positive findings on 68Ga DOTATATE PET/CT and should be considered as part of the differential diagnosis, even in an asymptomatic patient.
Keywords: False positive; gallium-68 DOTA-Tyr3-octreotate; neuroendocrine prostate cancer; neuroendocrine tumor; nuclear medicine; positron emission tomography/computed tomography; prostatitis